PENGGUNAAN TA’WIL, TARJIH DAN NASKH DALAM PEMAHAMAN HADIS - Melia Novera (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2021)
This study shows that Muslims need the methods used by scholars in taking hadith fiqh including the ta'wil, tarjih, and naskh methods. Ta'wil is a phrase about taking the meaning of lafadz which is probability supported by the proposition and makes a meaning stronger than the meaning pointed by lafadz dzahir. The explanation is according to Imam al-Ghazali. Furthermore, there are several takwil requirements, the base of ta’wil and the classification of ta’wil. Tarjh is to set an advantage on one side that is opposite each other. Or make something stronger. The term is to compare the signs that strengthen him in front of his opponent While the meaning of nasakh itself is canceling a law with the proposition that comes later. It extends to the discussion of the criteria of nasakhs and texts that do not accept the nasakh that includes the criteria of the nasakh itself.